THE EFFECT OF INDONESIAN MACROECONOMIC CONDITION AND INTERNATIONAL INTEREST RATE ON YIELD OF THE GOVERNMENT BOND IN US DOLLAR - Pramana, Farouq Widya; Nachrowi, Nachrowi D. (Journal of Indonesian Applied Economics, 2016)
This study analyzes the effect of Indonesian macroeconomic condition and international interest rate shocks on yield of the Government Bond in US Dollar. This study applies Vector Error Correction Model (VECM) using monthly data which consists of yield of the Government Bond in US Dollar, domestic interest rate, price level, real exchange rate, and international interest rate during the period of January 2006 to December 2013. The results show that domestic interest rate, price level, real exchange rate, and international interest rate have significant positive impacts on yield of the Government Bond in US Dollar and confirm the presence of the error correction mechanism in the yield of the Government Bond in US Dollar model that also indicates the existence of cointegration.